а)2sin²x-3sinx-2=0
Замена sinx=t
2t²-3t-2=0
D=3²+4×2×2=25
t₁= 3+√D÷4=3+5÷ 4=8÷4=2
t₂=3-√D÷4=3-5÷4=-2÷4=-0,5
Возвращаемся к замене
sinx=2 sinx=-0,5
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
4cos²x+4sinx-1=0
cos²x=1-sin²x
4( 1-sin²x)+4sinx-1=0
4-4sin²x+4sinx-1=0
-4sin²x+4sinx-1+4=0
-4 sin²x+4sinx+3=0 ÷(-1)
4sin²x-4sinx-3=0
Замена sinx=t
4t²-4t-3=0
D=4²+4×4×3=16+48=64
t₁=4+√D÷8= 4+8÷8=12÷8=1,5
t₂=4-√D÷8=4-8÷8= -4÷8=-0,5
Возвращаемся к замене
sinx=1,5 sinx=-1\2
решения нет х=(1)⁻k(cтепень)arcsin(-1\2)+πn,n∈Z
-1≤sinx ≥1 x=(1)⁻k × -π\6 +πn,n∈Z
Пусть А=2а,
вспомним формулы:
cos2а=cos²a-sin²a = cosA
sin2a=2sina*cosa = sinA
sin²a+cos²a=1 подставим в наше выражение:
1-cosA+sinA = (sin²a+cos²a) - (cos²a-sin²a) + 2sina*cosa=
sin²a+cos²a - cos²a+sin²a + 2sina*cosa=2sin²a + 2sina*cosa=
2sina(sina + cosa), вспомним, что а=А/2, получим ответ:
2sin(А/2) * ( sin(А/2) + cos(А/2) )